The Role of Tourism Destination Attributes in EnhancingTourist Loyalty Through Service Quality Experience at Tanjung Setia Beach Tourism Area, Pesisir Barat Regency, Lampung - Rangga Syatria; Yuniarti Fihartini; Dorothy Rouly H. Pandjaitan (International Journal of Economics, Business and Innovation Research, 2026)
This study examines the role of tourism destination attributes in enhancing tourist loyalty through service quality experience at Tanjung Setia Beach Tourism Area, Pesisir Barat Regency. Recognized as one of the world’s top surfing destinations, Tanjung Setia Beach faces challenges in accessibility and supporting facilities. A quantitative survey was conducted with 430 respondents, including domestic (76.74%) and international (23.26%) tourists who had visited the beach at least twice. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart PLS 4.0. The results show that destination attributes significantly influence both service quality experience (QSE) and tourist loyalty, with service quality experience mediating the relationship between destination attributes and loyalty. These findings indicate that effective management of attractions, accessibility, facilities, activities, and supporting services enhances tourist experience and fosters loyalty. Practically, this highlights the importance of improving infrastructure, diversifying activities, and enhancing service quality to maximize satisfaction. The study also contributes theoretically by reinforcing an integrative model linking destination attributes, service quality experience, and tourist loyalty, offering insights for sustainable tourism development at Tanjung Setia Beach.